Longitudinal study revealing motor, cognitive and behavioral decline in a transgenic minipig model of Huntington's disease - Baxa, Monika; Levinska, Bozena; Skrivankova, Monika; Pokorny, Matous; Juhasova, Jana; Klima, Jiri; Klempir, Jiri; Motlı K, Jan; Juhas, Stefan; Ellederova, Zdenka (Disease models & mechanisms, 2019)
Huntington's disease (HD) is an inherited devastating neurodegenerative disease with no known cure to date. Several therapeutic treatments for HD are in development, but their safety, tolerability and efficacy need to be tested before translation to bedside. The monogenetic nature of this disorder has enabled the generation of transgenic animal models carrying a mutant huntingtin (mHTT) gene causing HD. A large animal model reflecting disease progression in humans would be beneficial for testing the potential therapeutic approaches. Progression of the motor, cognitive and behavioral phenotype was monitored in transgenic Huntington's disease minipigs (TgHD) expressing the N-terminal part of human mHTT. New tests were established to investigate physical activity by telemetry, and to explore the stress-induced behavioral and cognitive changes in minipigs. The longitudinal study revealed significant differences between 6- to 8-year-old TgHD animals and their wild-type (WT) controls in a majority of the tests. The telemetric study showed increased physical activity of 4.6- to 6.5-year-old TgHD boars compared to their WT counterparts during the lunch period as well as in the afternoon. Our phenotypic study indicates progression in adult TgHD minipigs and therefore this model could be suitable for longstanding preclinical studies of HD.This article has an associated First Person interview with the first author of the paper.
Keywords: prasata; Behavior, Animal; Swine; modely nemocí na zvířatech; Physical Conditioning, Animal; jazyk; longitudinální studie; Large animal model; Phenotyping; psychický stres; Huntingtonova nemoc; kondiční příprava zvířat; Swine, Miniature; Huntington Disease; Huntington's disease; Animals, Genetically Modified; kognice; Animals; zvířata; pohybová aktivita; Stress, Psychological; Disease Models, Animal; Motor Activity; chování zvířat; Longitudinal Studies; Motor; geneticky modifikovaná zvířata; Cognitive and behavioral studies; Tongue; Cognition; miniaturní prasata